METHODOLOGICAL RECOMMENDATIONS ON THE TEACHING OF PHYSICAL EDUCATION IN VOCATIONAL SCHOOLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This scientific article gives methodological recommendations on the teaching of physical education in vocational schools in our country, attention to the education of a healthy generation, and the opportunities created.